Pengaruh Dukungan Sosial terhadap Penanganan Functional Gastrointestinal Disorders (FDGs) : Tinjauan Naratif - Herdian Putra, Ade (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2024)
Functional Gastrointestinal Disorders (FGIDs) are chronic conditions characterized by significant symptoms that affect the quality of life of sufferers. This study examines the role of social support in managing FGID symptoms through a comprehensive narrative review. The findings indicate that social support, including emotional, instrumental, and informational support, has a significant positive impact on the physical and mental well-being of individuals with FGIDs. Social support helps reduce stress and anxiety, which often exacerbate FGID symptoms, by lowering sympathetic nervous system activity and enhancing vagal nerve activity. The effectiveness of social support is influenced by cultural factors, economic conditions, and the stability of social relationships. The study also highlights the critical role of technology and social media in providing broader and more accessible social support, although it is essential to ensure that the information provided is trustworthy and evidence-based. Implications for clinical practice include the integration of social support into treatment plans and education for patients and families. Further research is needed to explore the specific mechanisms of social support and to develop innovative interventions. By understanding and leveraging the power of social support, we can help individuals with FGIDs better manage their conditions and improve their overall quality of life.